2015
DOI: 10.1080/15476286.2015.1076611
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA of the human sphingomyelin synthase 1 gene: Multiple splice variants, evolutionary conservatism and expression in different tissues

Abstract: The human sphingomyelin synthase 1 gene (SGMS1) encodes an essential enzyme that is involved in the synthesis of sphingomyelin and diacylglycerol from phosphatidylcholine and ceramide. Among the products of SGMS1, we found new transcripts, circular RNAs (circRNAs), that contain sequences of the gene's 5 0 untranslated region (5 0 UTR). Some of them include the gene's coding region and fragments of introns. An analysis of the abundance of circRNAs in human tissues showed that the largest transcripts were predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…To date, there is evidence that a substantial part of long ncRNA exists in a circular form [49][50][51][52][53][54]. Circular RNA (circRNA) is a newly discovered and relatively poorly studied class of long ncRNA, found predominantly in mammalian cells.…”
Section: Long Ncrnas and Circrnasmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, there is evidence that a substantial part of long ncRNA exists in a circular form [49][50][51][52][53][54]. Circular RNA (circRNA) is a newly discovered and relatively poorly studied class of long ncRNA, found predominantly in mammalian cells.…”
Section: Long Ncrnas and Circrnasmentioning
confidence: 99%
“…ceramide [59][60][61][62][63]. In addition to mRNAs providing protein synthesis, 13 circRNAs that predominantly contained sequences of the multi-exon 5′-untranslated region of the gene (5′-UTR) have been identified [54]. The RS-exons that participate in the multistep splicing of long introns of the gene were found within six circRNAs of the SGMS1 gene.…”
Section: A Model Of Circrna Formation With the Participation Of Recurmentioning
confidence: 99%
See 1 more Smart Citation
“… 52 Filippenkov et al. also showed that circRNAs containing sequences of the gene's 5′ untranslated region (5′UTR) of the human sphingomyelin synthase 1 gene ( SGMS1 ) were found predominantly in different parts of the brain, and regulated the function of the SGMS1 gene in the brain, 53 while the SGNS1 gene encodes a transmembrane protein participating in sphingomyelin synthesis, intracellular molecular transport regulation, cholesterol metabolism, cell proliferation, and apoptosis. 54-56 CircRNAs are very abundant in the mammalian brain, as well as through neuronal differentiation, especially in synapses, and with their high stability, neuronal termini might use them and they might perform as synaptic tags to maintain a molecular memory.…”
Section: The Role Of Circrna In Diseasesmentioning
confidence: 99%
“…Despite their abundance, predicting circRNAs remains burdensome and typically relies on bioinformatic tools identifying sequences across backsplice junctions from RNA sequencing data obtained upon depletion of ribosomal RNA 15 . Although this has resulted in the prediction of thousands of potential circRNAs in cell lines or whole organs of many species 6,11,13,[16][17][18][19] , this approach based on ribosomal RNA depletion has the critical limitation that reads that do not map on a backsplice junction cannot be assigned to a circular, as opposed to a linear, transcript resulting in the exclusion of the overwhelming majority of the sequencing data. In turn, this makes it impossible to reliably reconstruct neither the full sequence nor the expression level of large pools of circRNAs.…”
Section: Introductionmentioning
confidence: 99%